Tobacco menace near educational institutions of Mandya city, South Karnataka - B. R., Harish; M., Vinay; D., Ashwini; J., Bindiya; M. R., Mythily (International Journal Of Community Medicine And Public Health, 2018)
Background: Tobacco kills more than 7 million people a year. India has one of the world’s heaviest tobacco-related health burdens. The government of India has enacted the Cigarettes and Other Tobacco Products Act (COTPA) 2003 to control the factors which favor the use of tobacco products. The present study was taken up with the objective to determine the proportion of educational institutions having display boards prohibiting tobacco sales and use, having advertisements & tobacco selling outlets nearby and to assess the awareness regarding rules for tobacco sales among the persons selling tobacco products in these outlets. Methods: Cross-sectional study conducted from October to December 2017, in all the educational institutions of Mandya city using a pretested, structured questionnaire. Descriptive and inferential statistics was used for analysis. Results: Of the 92 educational institutions 13 (14.1%) had “No smoking” display boards. 30 (32.6%) had the display board that sale of tobacco products is prohibited within a radius of 100 yards of the educational institution. 146 tobacco selling outlets were present near the 71 educational institutions. 19 (13.0%) sellers knew that sale of tobacco products is prohibited within a radius of 100 yards of the educational institution. Conclusions: One sixth of the educational institutions had “No smoking” display boards and one third had display board that stated that the sale of tobacco products was prohibited within a radius of 100 yards of the educational institution. The awareness regarding sale of tobacco products was inadequate among the persons selling tobacco products.